Melphalan Culprit or Confounder in Acute Encephalopathy during Autologous Hematopoietic Stem Cell Transplantation? - Diógenes Alayón-Laguer; Melissa Alsina; Jose L. Ochoa-Bayona; Ernesto Ayala (Case Reports in Transplantation)
We report a case of a female patient with Durie-Salmon stage 3A/ISS stage I IgG kappa multiple myeloma (MM) who developed encephalopathy after high-dose melphalan and hematopoietic stem cell transplant (HSCT). The most common etiologies for encephalopathy such as infection, narcotic medications, metabolic-electrolyte disturbance, stroke, and central nervous system (CNS) hemorrhages were ruled out. The patient recovered from the altered mental status spontaneously. The possibilities of melphalan-induced encephalopathy versus critical-state delirium versus hypercytokinemia induce encephalopathy were contemplated.